Joint IterativeTx/Rx MMSE-FDE and ISICancellation for Single-Carrier Hybrid ARQ with Chase Combining. (6th September 2010) - Takeda Takeda, Kazuki Kazuki; Adachi Adachi, Fumiyuki Fumiyuki
Abstract : We propose a joint iterative transmit/receive (Tx/Rx) minimum mean square error (MMSE) frequency-domain equalization (FDE) and intersymbol interference cancellation (ISIC) suitable for single-carrier (SC) hybrid automatic repeat request (HARQ) with chase combining (CC). In the proposed scheme, a one-tap transmit MMSE-FDE and an iterative one-tap receive MMSE-FDE and ISIC are employed. Every time the retransmitted packet is received, a series of receive MMSE-FDE, antenna diversity combining, packet combining, and ISIC is carried out in an iterative manner by using updated receive MMSE-FDE weights in each iteration. The transmit MMSE-FDE weight is determined based on the prediction of the degree of residual ISI after the iteration process in a receiver. We theoretically derive a set of transmit and receive MMSE-FDE weights. We show by computer simulation that joint iterative Tx/Rx MMSE-FDE and ISIC achieves better packet error rate (PER) and higher throughput of SC-HARQ than the conventional Rx MMSE-FDE and ISIC.